Inovasi Nanokoloid Perak Hasil Biosintesis Menggunakan Ekstrak Tanaman Keladi Sarawak Dalam Bentuk Gel : Uji Stabilitas Fisik Dan Aktivitas Antibakteri Terhadap Staphylococcus aureus - Athiah Masykuroh; Dzawil Kamala, Sirna; Sintia Puspita, Rani (BIOMA : JURNAL BIOLOGI MAKASSAR, 2025)
Stability test of Physical and Antibacterial Activity against Staphylococcus aureus of the silver nanocolloid gel biosynthesized by Alocasia macrorrhizos plant extract has been conducted. The test was using cycling test method to estimate stability of the gel. The AgNO3 concentration used in the silver nanocolloid biosynthesis process is 0.05 M ; 0.10 M and 0.15 M. The nanocolloid was diluted 50% of the initial concentration and innovated into a gel form (formula I, II and III) then tested on physical evaluation and antibacterial activity against Staphylococcus aureus bacteria. The physical evaluation test include organoleptic, pH, homogeneity, viscosity, spreadability and hedonic test. The measurement of of the clear zone formed around the disc paper was carried out to determine it’s antibacterial activity. The results shows all variation’s value decreased at physical evaluation test but still meet the requirements except for viscosity test and shows decereased at antibacterial activity test against Staphylococcus aureus. Kata kunci : silver nanocolloids, gel, Alocasia macrorrhizos (L.), cycling test, staphylococcus aureus